Hubungan Semantik Kanji Ber-bushu Sanzui Hen (?) dengan Makna Air Kategori Kelas Kata Benda dalam J?y? Kanji - Ayu, Dhaniswari Ananta (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 25 No 1 (2025)DO - 10.24843/PJIIB.2025.v25.i01.p01, 2025)
The original meaning of kanji characters can be determined using bushu as one of the important elements in interpretation. This study aims to discover semantic relations which appear from kanji characters with sanzui hen (?) bushu which means water. Sources used in this research are limited to nouns and obtained from j?y? kanji of 2010 revision which covers 47 characters. The theories used are kanji formation, lexical decomposition, componential analysis of meaning, semantic relations, and semantic field. The study found that there are six types of semantic relations, namely: 1) High Semantic Relations 1 (HSR1): water, a clear, colorless, tasteless, and odorless object, with total of 1 character; 2) High Semantic Relations 2 (HSR2): objects in liquid form, with total of 12 characters; 3) High Semantic Relations 3 (HSR3): places that contain water, with total of 19 characters; 4) High Semantic Relations 4 (HSR4): objects that contain small amounts of water, with total of 3 characters; 5) High Semantic Relations 5 (HSR5): water which is merely used as a concept, with total of 4 characters; and 6) Low Semantic Relations (LSR): kanji characters which are totally unrelated to water, with total of 8 characters. In conclusion, although HSR appears the most, there is only one character that is categorized as HSR1 with its bushu. Moreover, there are even characters whose meanings are completely unrelated to water (LSR).